Introduction - Zhenchao Qian; Trevon Logan (RSF: The Russell Sage Foundation Journal of the Social Sciences)
U.S. Census 2020: Continuity and Change is the focus of this double issue of RSF: The Russell Sage Foundation Journal of the Social Sciences. This introduction briefly describes the broad socioeconomic changes between 2010 and 2020 in the United States and their implications for inequality, families, and American society. We then review the changes in employment, earnings, and education; housing and residential mobility; families and living arrangements; gender, sexuality, race-ethnicity, immigration, and rural America among others discussed in this issue. We highlight the areas of change, stemming from both changes in data availability and measurement and substantive material outcomes with a focus on whether the patterns follow the trends of past decades or change in new directions that signal more fundamental structural changes in American society.